HUBUNGAN KECEPATAN DAN EXPLOSIVE POWER OTOT TUNGKAI DENGAN HASIL LOMPAT JAUH GAYA JONGKOK PADA SISWA PUTRA KELAS VIII A SMPN 3 DUMAI - Ary Bayu Nugraha Bayu Nugraha; Saripin '; Ni Putu Nita Wijayanti Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : based on the result from the study, the reseacher find out result students not appropriate with expectation, it’s seen from the result of the study was making practice exam athletic jump away for male students VIII A at junior high school 3 Dumai. Many students can’t achievement of kkm the school has been determined, the reseacher goal is to determine the releastionship speed and explosive power leg muscles jump for the male students grade VIII A at junior high school 3 Dumai, the population from the study is 15 male students (total sampling). The reseacher used standing broad jump test on the study, speed run of 30 with thecnique jump the data analyzed with simple and double product moment, Based on the findings of the study of The lead with speed run has Relations Jump findings the male students on a class VIII junior high school Negeri 3 Dumai, where the findings that is rcount (0593)> From rtabel (0532). Then From the findings of The TIN has a leg muscle Explosive power relations Jump findings male students of Class VIII junior high school Negeri 3 A Dumai, where the findings that is rcount (0662)> From rtabel (0532). There is a relationship between the speed run And Explosive power leg muscles Jump findings away with the male students of Class VIII A students of junior high school Negeri 3 A Dumai, where the findings of That is r rcount (0753)> From rtabel (0532).Keywords: Speed run, leg muscle explosive power, Long Jump Results